2002
DOI: 10.1006/brln.2001.2512
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Contributions to Lexical Ambiguity Resolution: Evidence from Individuals with Complex Language Impairment Following Left-Hemisphere Lesions

Abstract: Nine individuals with complex language deficits following left-hemisphere cortical lesions and a matched control group (n ϭ 9) performed speeded lexical decisions on the third word of auditory word triplets containing a lexical ambiguity. The critical conditions were concordant (e.g., coin-bank-money), discordant (e.g., river-bank-money), neutral (e.g., day-bankmoney), and unrelated (e.g., river-day-money). Triplets were presented with an interstimulus interval (ISI) of 100 and 1250 ms. Overall, the left-hemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 23 publications
1
12
1
3
Order By: Relevance
“…For example, when words are embedded in sentences that are biased toward one meaning of a homonym, there is evidence to suggest that the LH is more likely to select the contextually-consistent meaning (Faust and Gernsbacher, 1996), regardless of meaning frequency (Faust and Chiarello, 1998), whereas the RH fails to select (but see also Coney and Evans, 2000). These VF studies with neurologically-intact participants thus seem to indicate that the LH controls meaning selection processes, and, in support of this conclusion, LH damage has been linked to meaning selection deficits (Copland, Chenery, and Murdoch, 2002;Swaab, Brown, and Hagoort, 1998). However, participants with unilateral RH damage have also been found to exhibit deficits in context-based meaning selection (McDonald et al, 2005;Tompkins et al, 2000), suggesting that the RH contributes essential functions as well.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 78%
“…For example, when words are embedded in sentences that are biased toward one meaning of a homonym, there is evidence to suggest that the LH is more likely to select the contextually-consistent meaning (Faust and Gernsbacher, 1996), regardless of meaning frequency (Faust and Chiarello, 1998), whereas the RH fails to select (but see also Coney and Evans, 2000). These VF studies with neurologically-intact participants thus seem to indicate that the LH controls meaning selection processes, and, in support of this conclusion, LH damage has been linked to meaning selection deficits (Copland, Chenery, and Murdoch, 2002;Swaab, Brown, and Hagoort, 1998). However, participants with unilateral RH damage have also been found to exhibit deficits in context-based meaning selection (McDonald et al, 2005;Tompkins et al, 2000), suggesting that the RH contributes essential functions as well.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 78%
“…These studies, along with evidence suggesting that LH damage is associated with meaning selection deficits (Copland et al, 2002;Swaab et al, 1998), point to a critical role for the LH in the control of meaning selection. However, deficits in context-based meaning selection have also been observed in patients with unilateral RH damage (McDonald et al, 2005;Tompkins et al, 2000).…”
Section: Hemispheric Asymmetries In Ambiguity Resolutionmentioning
confidence: 82%
“…When sentence context information is available to constrain the possible meaning of homonyms, VF studies with neurologically-intact participants suggest that the LH is more likely to select the meaning that is consistent with context (Faust and Gernsbacher, 1996;Faust and Chiarello, 1998), whereas the RH fails to select (but see also Coney and Evans, 2000). These studies, along with evidence suggesting that LH damage is associated with meaning selection deficits (Copland et al, 2002;Swaab et al, 1998), point to a critical role for the LH in the control of meaning selection. However, deficits in context-based meaning selection have also been observed in patients with unilateral RH damage (McDonald et al, 2005;Tompkins et al, 2000).…”
Section: Hemispheric Asymmetries In Ambiguity Resolutionmentioning
confidence: 90%
“…One study (29) used Filipino-English bilinguals to investigate cross-linguistic effects in the processing of English phonology. The seven studies of aphasia (3,10,14,19,34,48,50) represented in the special issue uncovered a variety of new phenomena and were distinguished by their use of diverse assessment techniques. Finally, one study (39) reported on the manner in which developmental dysphasia impacts the processing of verbs.…”
Section: Language Effectsmentioning
confidence: 99%